Femtosecond laser sintering Al nanoparticles: A multiscale investigation of combined molecular dynamics simulation and two-temperature model - Guo, Jianwu; Ji, Pengfei; Jiang, Lan; Lin, Gen; Meng, Yu (Powder technology, 2022)
The sintering process of Al nanoparticles subject to femtosecond laser irradiation is investigated by using a multiscale approach combining molecular dynamics simulation at atomistic scale and two-temperature model at continuum scale. The temporal evolutions of electron temperature and lattice temperature, atomistic snapshot and structural transformation are calculated to reveal the detailed spatiotemporal information on femtosecond laser sintering Al nanoparticles. Moreover, by studying the temporal evolutions of mean square displacement, radius ratio, shrinkage rate and gyration radius during the sintering process, the impacts of absorbed laser fluence and laser pulse width on the sintering process of Al nanoparticles are probed. The absorbed laser fluence is found to crucially induce whether the Al nanoparticles are to be sintered. Furthermore, the critical absorbed laser fluence to trigger sintering is determined. Whereas, the laser pulse width is found to bring almost no distinctive differences on the process and result of Al nanoparticles sintering.